Using CFD to investigate the effect of ducts on propeller performance - He, Ngo Van; Cong, Nguyen Chi; Loi, Luong NJoc (Journal of Naval Architecture and Marine Engineering, 2024)
Ducted propellers find widespread application across various vessels, such as fishing vessels, trawlers, and submarines, owing to their proven efficiency in propulsion systems. This paper explores the hydrodynamic impact of ducts on propeller performance through the application of a commercial Computational Fluid Dynamics (CFD) code. Additionally, an analysis of various turbulence models, including RNG k-ε, SST k-ω, and transition SST k-ω, was conducted to understand their effects on the calculated results. The propeller under consideration in this study possesses significant parameters: a diameter of 3.65 m, operating at 200 rpm, with an average pitch angle of 2.459 m and a boss ratio of 0.1730. The duct employed in the ducted propeller system features a NACA 4415 profile, chosen for its favorable hydrodynamic characteristics, making it well-suited for the propeller duct. The methodology involved the construction, meshing, and refinement of the geometry model for both the open water propeller and the ducted propeller system. Subsequently, the performance of these systems was analyzed using the RNG k-ε, SST k-ω, and transition SST k-ω RANS turbulence models. The study delves into the effects of the duct on the propeller's hydrodynamic features, as well as the influence of different turbulence models on the obtained results. The computed results presented encompass pressure distribution, hydrodynamic characteristics, and velocity profiles behind the propeller in various scenarios. The paper concludes with a comprehensive discussion of the effects of the duct on hydrodynamic features and the impact of different turbulence models on the results, providing valuable insights into the interplay between ducts and propeller performance. Journal of Naval Architecture and Marine Engineering, 21(2), 2024, P: 87-101